Histone retention, protein carbonylation, and lipid peroxidation in spermatozoa: Possible role in recurrent pregnancy loss. (3rd May 2016) - Mohanty, Gayatri; Swain, Nirlipta; Goswami, Chandan; Kar, Sujata; Samanta, Luna
ABSTRACT: Contribution from a defective paternal genome has been attributed to be an important cause for spontaneous recurrent pregnancy loss (RPL). Increased oxidative stress results in decreased detoxification and is a cause for damage to chromatin, proteins, and membrane lipids. The present study aimed to explore if there is a significant relationship between retained histones due to defective packaging of DNA in spermatozoa and oxidative stress. RPL patients ( n =16) with a history of ≥2 embryo losses before the 20th week of gestation and no female factor abnormality, and fertile healthy volunteers ( n =20) as controls were included in the study. A significant difference in the levels of protein carbonylation and lipid peroxidation together with an increased retention of histones in the experimental groups was noticed. Histone carrying sites for oxidative modification such as arginine and lysine might be responsible for disturbing the paternal epigenomic control during early stages of embryonic differentiation leading to abortion.